Acute responsivity of the serotonergic system to S-citalopram and positive emotionality—the moderating role of the 5-HTTLPR - Wielpuetz, Catrin; Kuepper, Yvonne; Grant, Phillip; Munk, Aisha; Hennig, Juergen (Frontiers in Human Neuroscience, 2013)
According to the idea that the central serotonergic system has a modulatory function on behavior and personality in general, we aimed to highlight its association to habitual positive emotionality. In a placebo-controlled double-blind and randomized cross-over neuroendocrine challenge design (n = 72 healthy males) we investigated the association of the central serotonergic responsivity, 5-HTTLPR-genotype as well as their combined effects on positive emotionality. Regression analyses revealed an involvement of the serotonergic system in positive emotionality. There was, however, no direct association between positive emotionality and cortisol responses to S-citalopram; rather 5-HTTLPR-genotype showed an association (p < .05). That is, positive emotionality scores increased with the number of s-alleles carried by the individuals. Most notable was the moderating role of 5-HTTLPR-genotype (p < .05) on the association between acute serotonergic responsivity and positive emotionality. Indeed, this association was only found in ss-homozygotes, in which the acute responsivity of the serotonergic system additionally seems to contribute to the level of positive emotionality (r = .70, p < .05). The findings correspond to previous research demonstrating that the 5-HTTLPR is not only involved in the negative-emotional aspects of behavior and temperament, but is associated, moreover, with positive affectivity – supporting the assumption of its valence-neutrality. In addition, our data are in line with the idea of possible influences of the 5-HTTLPR-genotype on early neuronal development. They also indicate the need for further studies in order to clearly elucidate the role of the serotonergic system and its subcomponents in the regulation of positive emotionality.